Mathematics barriers experienced by grade 3 children in some previously disadvantaged of school South Africa - Machaba, Maphetla M (Penerbit Universiti Kebangsaan Malaysia, 2019)
Children as early as Foundation Phase are unable to solve mathematical problems. The problem of poor Foundation Phase learner performance in mathematics is of international concern. One of the critical concerns noted by Annual National Assessment (ANA) is the concern about the understanding of teaching mathematics content in Foundation Phase. The aim of the paper is to examine the barriers experienced by Grade 3 children in mathematics computation in previously disadvantaged schools in South Africa. The study employed a qualitative study approach-using semi – structured interviews with three teachers in three schools. All the teachers consented to participate. The main findings of this study suggest that all the barriers to learning relate to poor mathematical language proficiency. Therefore, based on the findings, the methods of teaching mathematics should change, by including for example concrete objects. Furthermore, the training of mathematics teaching should be adapted so that it should be in line with the practical teaching in class.